SOSIALISASI KESADARAN MASYARAKAT AKAN BAHAYA DAN ETIKA PEMAKAIAN LISTRIK DI RUMAH PADA KELURAHAN TARATARA DUA - Ridwan, Ridwan; Nurmanita, Mutiara; Ticoh, Janne Deivy; Kilis, Billy M.H (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2024)
There is still a lack of public understanding regarding how to use electrical equipment at home and also ignorance about the dangers of electricity caused by the way it is used or indifference to maintaining and caring for electrical equipment in accordance with general regulations and operational standards for occupational safety and health. If left unchecked, it will of course cause an electric shock and can trigger a house fire due to electrical equipment and power sources. The aim of community service is to provide knowledge to the public regarding awareness in using electrical equipment at home and also the correct use of electricity sources to avoid electric shocks or damage to electrical equipment. This activity took place in Taratara Dua Village, Tomohon where the object of service was housewives, and farming and gardening activists with a total of 20 participants. The method used for this service is in the form of lectures supported by teaching aids in the form of work simulations in accordance with occupational safety and health and general electrical installation regulations regarding electricity, and questions and answers to the public. The results obtained by community service were 90.8% of the community understanding awareness of the ethics of using electrical equipment at home according to occupational safety and health and understanding the potential electrical dangers that occur at home. Thus, it turns out that after conducting community outreach about the dangers of electricity and the ethics of using electricity, it has been proven to have a positive impact on residents' knowledge of ethical awareness of using electrical equipment and understanding of electric shocks in accordance with operational standards, occupational health safety and general electrical installation regulations in using electrical equipment at home References Adhiem, M. A., Permana, S. H., & Faturahman, B. M. (2021). Pembangkit Listrik Tenaga Surya bagi Pembangunan Berkelanjutan. Jakarta: Publica Indonesia Utama. Arifianto, T., Akhwan, A., Sunardi, S., Sunaryo, S., Feryando, D. A., Arifidin, M. A. A., Triwijaya, S., & Moonlight, L. S. (2023). Pelatihan Instalasi Listrik Tegangan Rendah untuk Instalasi Listrik Bangunan Sederhana Bagi SMK Negeri 1 Wonoasri Madiun. Community Development Journal: Jurnal Pengabdian Masyarakat, 4(5), 11264–11271. https://doi.org/https://doi.org/10.31004/cdj.v4i5.19724 Citarsa, I. B. F., Satiawan, I. N. W., Wiryajati, I. K., & Seniari, N. M. (2020). Penyuluhan Pemakaian Peralatan Listrik Di Perumahan Kodya Asri Mataram. Jurnal Abdi Insani, 7(2), 139–144. https://doi.org/https://doi.org/10.29303/abdiinsani.v7i2.323 Hakim, A. R., & Febriyanto, K. (2020). Hubungan Pengetahuan dengan Kepatuhan Penggunaan APD pada Pekerja di PT. Galangan Anugrah Wijaya Berjaya Samarinda. Borneo Studies and Research, 2(1), 446–452. Hasibuan, A., Siregar, W. V., & Sayuti, M. (2023). Pemanfaatan Energi Angin Untuk Pembangkit Energi Listrik Di Daerah Kepulauan Menggunakan Kincir Angin Skala Kecil. Jakarta: Feniks Muda Sejahtera. Henong, S. B., Patiraja, A. H., & Yunus, A. M. (2019). Penerapan Penggunaan Alat Pelindung Diri Bagi Para Siswa Kursus Perbengkelan Dan Menjahit Suluh Labur Kabupaten Belu Nusa Tenggara Timur. Jurnal Online Sekolah Tinggi Teknologi Mandala, 14(1), 121–127. https://ejournal.sttmandalabdg.ac.id/index.php/JIT/article/view/146 Husin, A., Andriani, D. S., Wiranti, W., Rahmadona, N., Wahyuni, S. A., Hardiansyah, A., Ariansyah, D., & Akbar, E. B. (2023). Edukasi Perilaku Hemat Energi Sebagai Upaya Tanggap Perubahan Iklim Pada Ibu Rumah Tangga di Desa Sakatiga Seberang Kabupaten Ogan Ilir. JOURNAL OF SRIWIJAYA COMMUNITY SERVICE ON EDUCATION (JSCSE), 2(1), 45–52. https://doi.org/https://doi.org/10.36706/jscse.v2i1.759 Khotimah, K. (2017). Wujud bela negara melalui pendidikan budaya hemat energi. Jurnal Pertahanan Dan Bela Negara, 7(3), 51–66. https://doi.org/https://doi.org/10.33172/jpbh.v7i3.230 Milah, A. S. (2023). Keselamatan Pasien Dan Keselamatan Kesehatan Kerja (K3). Tasikmalaya: Edu Publisher. Putranta, H., Wahiddayah, W. N., Yuliyani, L., Maheswari, N. Z., Muna, N., & Nada, A. K. (2024). Modul Edukasi Mitigasi Bencana. Yogyakarta: UIN Sunan Kalijaga Yogyakarta. Putri, L. A. K. (2018). Pengaruh program Sekolah Adiwiyata terhadap perilaku peduli lingkungan siswa di SMA Negeri 2 Pringsewu [Fakultas Ilmu Sosial dan Ilmu Politik]. https://digilib.unila.ac.id/32064/ Sakti, O., & Sukartini, N. M. (2020). Karakteristik Individu dan Perilaku Peduli Lingkungan: Penggunaan Listrik. IJEEM-Indonesian Journal of Environmental Education and Management, 5(1), 34–48. https://doi.org/https://doi.org/10.21009/IJEEM.051.03 Santoso, A. D., & Salim, M. A. (2019). Penghematan Listrik Rumah Tangga dalam Menunjang Kestabilan Energi Nasional dan Kelestarian Lingkungan Household Electricity Savings to Support National Energy Stability and Environmental Sustainability. Jurnal Teknologi Lingkungan, 20(2), 263–270. https://doi.org/https://doi.org/10.29122/jtl.v20i2.3242 Uyun, S., Octavia, S. A., Hilaliah, L., & Muharom, A. (2020). Manajemen Sekolah: Madrasah Adiwiyata. Yogyakarta: Deepublish. Wahyuningrum, K. (2017). Peran Humas PT. PLN (PERSERO) Area Samarinda dalamProgram Hemat Listrik di Kota samarinda [Universitas Mulawarman]. https://ejournal.ilkom.fisip-unmul.ac.id/site/wp-content/uploads/2018/01/Skripsi Khairiyah-157 (01-04-18-04-16-22).pdf